Back of the envelope calculations on the proposed Swansea Bay Tidal Lagoon - Adcock, T (2014)
This note presents some simple back of the envelope calculations on the power potential of the Swansea Bay Tidal lagoon as per the proposal submitted for planning permission in early 2014. The purpose of this note is to do a quick and crude reality check on the numbers presented by the developers. It is not intended as an in depth analysis or criticism as I have neither the information or the time to carry this out.